Technical analysis of a hybrid solid oxide fuel cell/gas turbine cycle - Junior, Amauri Menezes Leal; Leal, ElisÃ¢ngela Martins; Bortolaia, LuÃs AntÃ´nio (International Journal of Applied Power Engineering (IJAPE), 2021)
This paper shows a technical analysis of a direct internal reforming solid oxide fuel cell (DIR-SOFC) and a gas turbine (GT) system. The technical analysis consists of an energy and exergy analysis of the system. Equilibrium calculations are made to find the ranges of inlet steam/fuel ratio and the operational current density of the fuel cell. After that, a hybrid system consists of a DIR-SOFC and a GT is evaluated using a computer simulation at the design point. The results showed that the fuel cell is the main power producer system, the high energy efficiency (around 62%) and exergy efficiency (around 58%) is achieved by the hybrid cycle compared to fuel cell efficiency (about 40%) and the gas turbine (around 38%). The power ratio of the fuel cell / gas turbine was 1.50. An analysis varying the fuel cell current density and the gas turbine pressure ratio was performed showing that the fuel cell power production decreases with increasing current density when the gas turbine becomes the main power producing equipment. However, the system energy efficiency decreases with the reduction of power produced by the fuel cell. Finally, it is shown that the computer simulation of the hybrid system may represent a quick and economic feasible way to investigate it.